Kelompok Dasawisma Sebagai Wadah Manajemen Ekonomi Masyarakat Guna Meningkatkan Kesejahteraan Dan Kesehatan Masyarakat Di Wilayah Kota Pekalongan - Rahmawati, Ferida; Nurlaela, Emi (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Humans are social creatures, social creatures. Community life can be seen in neighbourly life. These neighbouring community groups require economic management so that the welfare and health of the community in the area are achieved. Managing a community’s economy requires the thoughts, energy and time of people who can be trusted. Management can be carried out in the Dasawisma group. This service activity aims to improve order in financial management, including communities in dasawisma groups. Dasawisma’s activities involve regular meetings every month, alternating places. The activity began with an opening delivered by the chairman of Dasawisma. The next activity is to report on each field. Each sector conveys income funds and expenditure funds that have been used in the previous month, such as activities to visit sick residents, activities to visit births if a resident gives birth, takziyah activities, as well as activities carried out by residents in the previous month that require expenditure from funds collected from a dasawisma group. Dasawisma activities are carried out once a month, managing the community economy for community welfare and health, financial management of death funds, welfare funds, loan funds for residents in need, environmental cleanup funds, security funds and other funds. Management is carried out by dasawisma administrators who consist of women who live in the area. Documentation is carried out in each field that manages finances, so that it can be documented well, orderly and responsibly, for the welfare of the community and the health of the local community. Dasawisma activities run conducively, activities include managing the community economy. Good, orderly management of the community economy, increasing public trust.